The Text Book Project for African Music - Tracey, Hugh (International Library of African Music, 1966)
For many years it has been felt that one of the more important advances in African cultural affairs would be to codify the logic which lies behind the creation of indigenous styles of music and thus to bring it naturally, without prejudice, into the realm of African education.
Keywords: Ethnomusicology; Music; Textbooks; Africa; African Music